PENGARUH KUALITAS PELAYANAN BPJS KESEHATAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI UPTD PUSKESMAS BANDAR KOTA PAGAR ALAM (Ekonomia, 2021)
The aims of this study were 1) to determine the effect of BPJS Health service qualityon outpatient satisfaction at UPTD Bandar Kota Pagar Alam Health Center, 2) todetermine the relationship between BPJS Health service quality and outpatientsatisfaction at UPTD Puskesmas Bandar Kota Pagar Alam. The research methodused is associative research type. Primary data were obtained from questionnairesdistributed to 96 respondents who were outpatients at the UPTD Puskemas BandarKota Pagar Alam. Secondary data was obtained through literature study (relevantbooks and literature) and agency internal data. The indicators used were obtainedfrom this study, namely the dimensions of BPJS Service Quality (X) and thedimensions of Patient Satisfaction (Y). Based on the results of the analysis ofresearch that has been done, that the correlation calculation in this study, the effect ofservice quality (X) on patient satisfaction (Y) the correlation value of 0.608 meansthat there is a correlation value in a strong level and a positive sign on the correlationcoefficient indicates a unidirectional relationship between quality service (X) withpatient satisfaction variable (Y) at UPTD Puskesmas Bandar Kota Pagar Alam.There is an influence of service quality on patient satisfaction of UPTD PuskesmasBandar Kota Pagar Alam. Based on this statement, it means that Ha can be accepted.